A Bibliometric Study of Publications on Adoption of FinTech Using VOSviewer. (June 2023) - Khurana, Khushbu
More scholarly articles are being published as FinTech becomes more widely used. It is especially crucial to assess the quality of this large number of research articles and gather useful data. Thus, a bibliometric analysis of these articles may offer insight into current research trends and relevant themes. Globally existing literature about FinTech published between 2019 and 2022 was perused in the SCOPUS database. The articles' bibliometric analysis was carried out using a VOSviewer. Of the 4, 532 keywords, 463 met the threshold. The keywords that appeared most were "fintech" (total link strength 2, 600), "blockchain" (total link strength 533), "financial inclusion" (total link strength 436), and "financial technology" (total link strength 325) which has a strong link with mobile banking, financial stability, and financial literacy. The present growth patterns indicate a significant rise in the number of international FinTech publications. Within this significant field, the United States produced the most noteworthy contribution.